2010
DOI: 10.1021/jp1052369
|View full text |Cite
|
Sign up to set email alerts
|

FRET-Derived Ratiometric Fluorescent K+ Sensors Fabricated from Thermoresponsive Poly(N-isopropylacrylamide) Microgels Labeled with Crown Ether Moieties

Abstract: We report on the fabrication of ratiometric fluorescent K(+) sensors based on thermoresponsive poly(N-isopropylacrylamide) (PNIPAM) microgels covalently incorporated with K(+)-recognizing 4-acrylamidobenzo-18-crown-6 residues (B18C6Am), fluorescence resonance energy transfer (FRET) donor dyes, 4-(2-acryloyloxyethylamino)-7-nitro-2,1,3-benzoxadiazole (NBDAE), and rhodamine-B-based FRET acceptors (RhBEA) by utilizing K(+)-induced changes in microgel volume phase transition (VPT) temperatures. P(NIPAM-B18C6Am-NBD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 61 publications
0
61
0
Order By: Relevance
“…Yin et al 91 recently reported on the fabrication of ratiometric fluorescent K þ sensors based on thermoresponsive PNIPAM microgels covalently incorporated with K þ -recognizing 4-acrylamidobenzo-18-crown-6 residues (B18C6Am), fluorescence resonance energy transfer (FRET) donor dye, NBDAE, and rhodamine B-based FRET acceptor (RhBEA) by utilizing K þ -induced changes in microgel VPT temperatures. The spatial distance between fluorescent donors and acceptors (NBDAE and RhBEA) within microgels can be tuned via thermoinduced collapse and swelling of thermoresponsive microgels above and below VPT temperatures, leading to the facile modulation of FRET efficiencies (Figure 7).…”
Section: Responsive Polymer-based Sensors Via Supramolecular Recognitionmentioning
confidence: 99%
“…Yin et al 91 recently reported on the fabrication of ratiometric fluorescent K þ sensors based on thermoresponsive PNIPAM microgels covalently incorporated with K þ -recognizing 4-acrylamidobenzo-18-crown-6 residues (B18C6Am), fluorescence resonance energy transfer (FRET) donor dye, NBDAE, and rhodamine B-based FRET acceptor (RhBEA) by utilizing K þ -induced changes in microgel VPT temperatures. The spatial distance between fluorescent donors and acceptors (NBDAE and RhBEA) within microgels can be tuned via thermoinduced collapse and swelling of thermoresponsive microgels above and below VPT temperatures, leading to the facile modulation of FRET efficiencies (Figure 7).…”
Section: Responsive Polymer-based Sensors Via Supramolecular Recognitionmentioning
confidence: 99%
“…In one such example, PNIPAm microgels were modified to incorporate potassium ion recognizing 4-acrylamidobenzo18-crown-6 residues (B18C6Am) and then a FRET pair of fluorophores (4-(2-acryloyloxyethylamino) -7-nitro-2,1,3-benzoxadiazole (NBDAE), and rhodamine-B-based FRET acceptors (RhBEA)) [134]. The key operational feature is the fact that the polymer LCST is directly affected by the K þ ion concentration, increasing by~9 C as the K þ concentration increased from 0 to 300 μM.…”
Section: Swelling and Assemblymentioning
confidence: 99%
“…Ratiometric fluorescent temperature sensing is more and more popular with potential advantages. For the ratiometric fluorescent temperature sensing based on the fluorescence resonance energy transfer (FRET) mechanism, multi-color fluorescence of NIPA-based polymer temperature sensors were reported [24][25][26][27]. In these studies, only one thermo-responsive monomer NIPA was used, which might limit the range of the temperature sensor.…”
Section: Introductionmentioning
confidence: 99%